What's the signification of nuclear vacuoles in human sperm? - Franco, J. G. [UNESP]; Baruffi, R. L R; Mauri, A. L.; Petersen, C. G. [UNESP]; Oliveira, J. B A; Vagnini, L. (My University, 2008)
The aim of this study was to determine the extent of DNA fragmentation and the presence of single/denatured or double stranded of DNA in sperm with large nuclear vacuoles (LNV) selected by high-magnification. A total of 30 patients had fresh semen samples prepared by discontinuous concentration gradient. Sperm with normal nucleus (NN) and LNV were selected at 8400x magnification and placed in different slides. DNA fragmentation was determined by TUNEL assay. Denatured and double stranded DNA was identified by acridine orange fluorescence method. The percentage of DNA fragmentation in LNV sperm (29%) was significantly higher (P<0.001) than NN sperm (15.8%). Therefore, cleavage of genomic DNA in low molecular weight DNA fragments (mono and oligonucleosomes), and single strand breaks (nicks) in high molecular weight DNA occur more frequently in LNV. Identically, the percentage denatured stranded DNA in sperm with LNV (67.9%) was significantly higher (P <0.0001) than NN sperm (33%). The high level of denatured DNA in sperm with LNV suggests precocious decondensation and disaggregation of sperm chromatin fibers. Our results support an association between LNV sperm and DNA damage, and the routine selection and injection of morphological motile sperm at high magnification for ICSI. The adverse effect (DNA fragmentation or denaturation) leads to concern particularly about the possibility of iatrogenic transmission of genetic abnormalities. Copyright - SBRA - Sociedade Brasileira de Reprodução Assistida.
Keywords: Denatured stranded DNA; DNA fragmentation; Human sperm; ICSI; Nuclear vacuoles; acridine orange; double stranded DNA; genomic DNA; single stranded DNA; cell nucleus; cell vacuole; DNA cleavage; DNA damage; DNA denaturation; fluorescence; genetic disorder; human; iatrogenic disease; male; nick end labeling; sperm